MHC-class I-restricted CD4 T cells: a nanomolar affinity TCR has improved anti-tumor efficacy in vivo compared to the micromolar wild-type TCR - Soto, Carolina M. (Springer-Verlag, 2012)
Clinical studies with immunotherapies for cancer, including adoptive cell transfers of T cells, have shown promising results. It is now widely believed that recruitment of CD4(+) helper T cells to the tumor would be favorable, as CD4(+) cells play a pivotal role in cytokine secretion as well as promoting the survival, proliferation, and effector functions of tumor-specific CD8(+) cytotoxic T lymphocytes. Genetically engineered high-affinity T-cell receptors (TCRs) can be introduced into CD4(+) helper T cells to redirect them to recognize MHC-class I-restricted antigens, but it is not clear what affinity of the TCR will be optimal in this approach. Here, we show that CD4(+) T cells expressing a high-affinity TCR (nanomolar K (d) value) against a class I tumor antigen mediated more effective tumor treatment than the wild-type affinity TCR (micromolar K (d) value). High-affinity TCRs in CD4(+) cells resulted in enhanced survival and long-term persistence of effector memory T cells in a melanoma tumor model. The results suggest that TCRs with nanomolar affinity could be advantageous for tumor targeting when expressed in CD4(+) T cells.